2022
DOI: 10.1101/2022.10.24.513258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-specific effects of voluntary wheel running on behavior and the gut microbiota-immune-brain axis in mice

Abstract: Physical exercise has been positioned as a promising strategy to prevent and/or alleviate anxiety and depression, but the mechanisms underlying its effects on mental health have yet to be entirely determined. Although the prevalence of depression and anxiety in women is about twice that of men, very few studies have examined whether physical exercise could affect mental health differently according to sex. This study examined, in mice, the sex-specific effects of voluntary exercise on body weight, depressive- … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…The microbial strain that was highly responsive to PoWeR training, Muribaculaceae bacterium DMS 103720, is a member of the family Bacteroidales (originally noted as S24-7), which have the capacity to produce succinate, acetate, and propionate through fermentation of carbohydrates (Lagkouvardos et al, 2019;Ormerod et al, 2016). Previous studies have also found that voluntary wheel running results in a significant increase in Muribaculaceae (Lamoureux et al, 2017;Williams et al, 2023). In these studies, as well as the present study, mice ran on average 7-13 km/day.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial strain that was highly responsive to PoWeR training, Muribaculaceae bacterium DMS 103720, is a member of the family Bacteroidales (originally noted as S24-7), which have the capacity to produce succinate, acetate, and propionate through fermentation of carbohydrates (Lagkouvardos et al, 2019;Ormerod et al, 2016). Previous studies have also found that voluntary wheel running results in a significant increase in Muribaculaceae (Lamoureux et al, 2017;Williams et al, 2023). In these studies, as well as the present study, mice ran on average 7-13 km/day.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research suggests that changes in the gut microbiota are associated with emotional states, as seen in depression, anxiety, and fearfulness disorders, where the gut microbiota composition differs from that of healthy individuals ( Dinan and Cryan, 2013 ). Voluntary wheel running exercise was shown to alleviate depressive and anxious behaviors in mice by positively affecting the gut microbiota and reducing levels of intestinal pro-inflammatory cytokines ( Williams, et al, 2023 ). Changes in the gut microbiota structure are thought to influence intestinal immune responses ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%